SCIENTIFIC RELATION WORKSITE PHYSICAL ACTIVITY IN BOARDING OF KNOWLEDGE MANAGEMENT (Fiep Bulletin - online, 2015)
This investigation aimed to examine the relationship of the trajectory of worksites with its scientific basis, through the production of lexical knowledge management approach. A descriptive qualitative research study was established based on the analysis of jobs obtained from the public called. For analysis, we used the lexical SPHINX & EURECA® V. 5. The analysis software allowed us to assess the phenomenon. Present as a framework capable of training and knowledge building in recent years is not generating new knowledge from the interaction between tacit knowledge and explicit knowledge.
Keywords: Work site exercise; Work; knowledge management.